A client-centered approach in home care for older persons – an integrative review. (1st October 2020) - Sanerma, Päivi; Miettinen, Sari; Paavilainen, Eija; Åstedt-Kurki, Päivi
Abstract: Objective: To describe and synthesize client-centered care and service in home care for older persons. Methods: The study was an integrative review using the guidelines for literature reviews by the Joanna Briggs Institute. The research process followed the Whittemore and Knafl framework and PRISMA toolkit in the selection of eligible articles. The CINAHL, Medline, Scopus, Web of Science and Social Sciences abstracts were searched for articles published between January 2007 and May 2020 according to previously designed search strategies. In total, 24 articles were deemed relevant for an analysis using a thematic analysis. Results: The analysis resulted in four themes with sub-themes which revealed that client-centered care and service in home care consist of: 1) Clients' involvement in their own care; self-care, decision-making, satisfactory daily life, 2) Family members' and care partners' participation in care; family members' and care partners' commitment to care, family members' and care partners' competence in care, 3) Communication and co-operation; communication models, empowerment, partnership, and 4) Evidence-based service competence; delivery and organization of services, implementation of services, versatile clinical skills, quality outcomes and personnel wellbeing. Conclusions: According to the results, achieving client-centered care and service in home care requires the realization of all of the above aspects. The practice of nursing must better identify all dimensions of client-centered care and take these into account in the delivery of home care services. KEY POINTS: Client-centeredness is a fundamental value and the basis of nursing and care in home care provided for older persons This paper: deepens and structures the concept of client-centered care in the context of home care. assists professionals to understand the factors behind client-centered care within the home care environment. provides deeper understanding of the roles of the older person, family members, and the service system in developing client-centered services in home care for older persons.